2013
DOI: 10.1111/j.1728-4465.2013.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder and Provider Views Regarding Pericoital Contraceptive Pills in India and Uganda

Abstract: The development of pericoital contraceptive pills is under consideration to address unmet need for family planning, especially among women who have infrequent sexual intercourse. Pericoital pills, an oral contraceptive taken 24 hours before or after intercourse, would be a potentially desirable contraceptive option because it could provide convenience, discretion, and female control over contraceptive use. To gauge receptivity to pericoital contraception, a total of 49 in-depth interviews and 5 focus group dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Importantly, one study demonstrated that the pregnancy prevention efficacy of on-demand oral levonorgestrel was similar to that seen with typical use of daily oral contraceptive pills ( Halpern et al., 2014 ). Key stakeholders and health care providers also agree that an event-driven method fills an important gap in women’s reproductive health products ( Cover et al., 2013a ). An on-demand topical prevention product has the potential to provide greater flexibility to meet end user’s needs, potentially leading to increased overall uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, one study demonstrated that the pregnancy prevention efficacy of on-demand oral levonorgestrel was similar to that seen with typical use of daily oral contraceptive pills ( Halpern et al., 2014 ). Key stakeholders and health care providers also agree that an event-driven method fills an important gap in women’s reproductive health products ( Cover et al., 2013a ). An on-demand topical prevention product has the potential to provide greater flexibility to meet end user’s needs, potentially leading to increased overall uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compliance might be easier given that pill use is triggered by a specific event, and the pill could be used discreetly, without the cooperation or knowledge of a partner, which is not the case for other coital-dependent methods (i.e., condoms). Most critically, there is evidence that women are already using currently available levonorgestrel (LNG) products off-label (i.e., emergency contraception pills (ECP)) as their main form of contraception (Cover et al 2013b;Vandermark Moore and Chan 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most critically, there is evidence that women are already using currently available levonorgestrel (LNG) products off‐label (i.e., emergency contraception pills (ECP)) as their main form of contraception (Cover et al. 2013b; Vandermark Moore and Chan 2019).…”
Section: Introductionmentioning
confidence: 99%